Development of polymorphic microsatellite markers and their use in collections of Erianthus arundinaceus in China. (30th December 2016) - Zhang, Jian‐Bo; Yan, Jia‐Jun; Shen, Xiao‐Yun; Bai, Shi‐Qie; Li, Da‐Xun; Zhang, Yu; You, Ming‐Hong; Zhang, Yu
Abstract: Erianthus arundinaceus (Retz.) Jeswiet is not only a candidate plant for sugarcane breeding programs, but also a potential bioenergy grass. However, there are no simple sequence repeat (SSR) markers for E. arundinaceus, and information on genetic structure essential in genetics based on Chinese wild germplasm is limited. Therefore, in this study, 15 polymorphic microsatellite markers for E. arundinaceus were developed, and genetic variation and genetic structure of Chinese wild E. arundinaceus was studied. Genetic variation of 164 individuals of 18 populations collected from natural habitats in six Chinese provinces was analyzed using developed SSR markers, which generated 105 polymorphic bands. The numbers of alleles per locus ranged from 6 to 11 with a mean of 9. Among and within the populations, the percentage of polymorphic bands was 91.18% and 46.45%, effective number of alleles was 1.63 and 1.30, Shannon's information index was 0.52 and 0.25, respectively. The populations were clustered into seven groups exhibiting a high level of genetic differentiation, which was highly associated with geographic origins of respective germplasm populations, and was significantly associated with geographic distances between the populations. The developed SSR markers had advantages in revealing genetic diversity and the variance among populations of Chinese E. arundinaceus . Large genetic variation among Chinese E. arundinaceus germplasm and the genetic structure of E. arundinaceus populations effected by geographic landforms and environments were revealed, which will be highly valuable in genetic improvement and the genetics research.